Properties Of Polyphenoloxidase Of Sugarcane And Development Of Methods To Prevent Discolouration Of Juice - Hoque, Mohammad Shamsul (1998)

(untitled)
The objective of the research was to develop a method to extend the shelf life of freshly extracted sugarcane juice. The work focused on understanding the properties of sugarcane juice as well as determining methods of preserving the colour. Polyphenoloxidase (PPO) from sugarcane juice was extracted, partially purified and characterised. Results indicated that the temperature for optimum PPO enzyme activity was 30°C at pH 7.6. Heat inactivation studies showed that enzyme lost 50% activity by exposure to 80, 75, 70 and 65°C for 1 .2, 2.8, 3.6 and 7.8 min, respectively. The use of ascorbic acid (0.5mM concentration), erythorbic acid (0.5mM concentration) and sodium metabisulphite (0.5mM concentration) inhibited the browning reaction 80%, 74% and 92%, respectively.The effect of different blanching conditions on the quality of juice was also investigated. Sugacane was blanched at various temperatures and time intervals using both steam ( 100 °C) and hot water (75°C, 80 °C and 85 °C). After blanching the juice was analysed for chlorophyll content, colour, PPO activity and tannin content and sensory evaluated for colour and taste. Unpeeled sugarcane stems which were steam blanched for 13±1 min yield the highest quality juice.